Assessing Apparent Equilibrium Concentrations in Cementation of Trace Pd, Pt, Au, and Rh from Nitrate Solutions Using Mg, Al, Fe, and Zn - Konrad Wojtaszek; Adrianna Pach; Tomasz Michalek; Kamil Dudek; Marek Wojnicki (Metals, 2024)
This study explores the impact of nitrate ions on the efficiency of cementing noble metals from diluted waste solutions at a temperature of 30 °C. The research involved measuring the effectiveness of different cementing metals (such as Zn, Al, Mg, and Fe) in the presence of nitrate ions by assessing the change in metal ion concentrations before and after the cementation process using spectrometric analysis. Initial concentrations of noble metals ware Pt = 5 ppm, Au = 7.5 ppm, Pd = 5 ppm, and Rh = 1 ppm. Kinetic studies revealed that 24 h is adequate to achieve apparent equilibrium in solutions with pH 2 and 1 M nitrate ion content. The study identified significant recovery losses for gold and platinum in nitrate solutions, underlining the necessity of nitrate-free solutions in recycling. Zinc and magnesium were effective in cementing Pd and Rh, while aluminum was efficient for Pt reduction in each condition. Complete removal of Au was not achieved with any tested metal, indicating a need for alternative methods.